Answer:
p(-5)=-11,987
p(3)=-227
Explanation:
To find the value of the function p(-5) just substitute x=-5 into the function expression instead of x:
![p(-5)=2\cdot (-5)^5-9\cdot (-5)^4-2\cdot (-5)^2+12\cdot (-5)-2=\\ \\=-6,250-5,625-50-60-2=-11,987](https://img.qammunity.org/2020/formulas/mathematics/high-school/llcwi6fk2j33gzr2i90f4oclj09yrierjt.png)
To find the value of the function p(3) just substitute x=3 into the function expression instead of x:
![p(3)=2\cdot 3^5-9\cdot 3^4-2\cdot 3^2+12\cdot 3-2=\\ \\=486-729-18+36-2=-227](https://img.qammunity.org/2020/formulas/mathematics/high-school/i3c7qkt5wrfu627ozajuvzg2ulrwpxqu5x.png)